EVALUATION OF THE IMPLEMENTATION OF ACADEMIC SUPERVISION PROGRAMS IN THE LEARNING PROCESS - HAKIM, Sherly Nur; KHULUQO, Ihsana El; BUNYAMIN, Bunyamin (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2024)
The aim of the research is to describe the evaluation of the Academic Supervision Program in the LearningProcess. The supervision carried out is limited to fulfilling the administrative duties and functions of the principaland not yet improving and developing teacher professionalism. So that teacher motivation to improveperformance, make improvements and develop themselves, especially in the learning process, is not yet optimal.This research uses the CSE-UCLA research model focused on four process stages, namely planning, process,formative and summative, suitable for use in evaluating learning programs at Kindergarten Pembina IV, SetuDistrict, South Tangerang City. The results of academic supervision carried out include the following: (a) Understanding the concepts, principles and basic theories of creative, innovative learning (b) Guiding teachers in compiling the syllabus for each area of development (c) Guiding teachers in choosing and using strategies that can develop various student potentials,(d) Guiding teachers in carrying out learning activities (e) Guiding teachers in managing and developingknowledge with ICT. 2) Academic supervision with a mentoring method can provide a solution to the problemsfaced by teachers so far and is the right strategy to improve the quality of learning. 3) Evaluation of the academicsupervision program including: a) Context Evaluation. b). Input Evaluation. c) Process Evaluation. d) ProductEvaluation. 4) The impact of academic supervision carried out by the kindergarten head in increasing teachercreativity was obtained by information that: academic supervision planning includes activities in determininggoals, objectives, organizing activities and determining time.